3d Scanner App For New Product Development Due To Covid-19 Pandemic - Shukry, Mohamad Danial Mohd (Universiti Sains Malaysia, 2021)
The Pandemic COVID-19 that has occurred in the world has affected all the people in the world whereas in the community but also in the economy. The movement limited control that has been applied by most of the country has been instructed to reduce and prevent the infection among the community. Therefore, a new product should be developed for civilians that will give benefit and value to the society during and after the Pandemic of COVID-19. Therefore, there is a space for such a product to be developed and commercialized. A survey has been conducting to the customer where the customer will have to fulfill all their need and problem. The result will be analyzed and the tally with the limitation of movement has created a new method to understanding the available product by implementing the 3D scanner application where the reverse engineering will be conducted on the target part model. Results show that the survey has provided a few justifications which give a chance for the product development. A new mechanism of door system has been created with the implementation of a 3D scanner application. Several studies have been made on the mechanism of the new mechanism of the door system. This project is the first step in developing a fully functional door mechanism that tally with the pandemic situation.